Assessing selected quality of life factors of nursing home residents in Turkey - LÜLECİ, NİMET EMEL (ELSEVIER IRELAND LTD, 2008)
As a result of improved public health and medical advances, not only has life expectancy among older people increased, but the importance of quality of life in terms of health in later life has also increased. The aim of this study was to investigate the relationship between socio-demographic factors, health-related behaviors, residents' satisfaction, and functional disability levels among elderly people living in nursing homes in Turkey using the World Health Organization's Quality of Life-BREF (WHOQOL-BREF). Data regarding socio-demographic characteristics, chronic health problems, health-related behaviors (smoking, alcohol consumption, physical activity, etc.) were collected from the study group (N = 107) by a structured questionnaire during face-to-face interviews. Dependencies in activities of daily living (ADL) of the study group were also assessed using Katz's ADL index. The mean WHOQOL-BREF scores were significantly higher in participants who had independence in performing ADL (bathing, dressing, toileting, transfer, continence, feeding) (p < 0.0001, p < 0.0001, p < 0.0001, p < 0.001, p < 0.0001, and p < 0.001, respectively). It was found that WHOQOL-BREF scores were positively associated with having physical exercise habits and residents' satisfaction with nursing homes; being dependent in dressing were significant predictors of in the study (R-2: 0.38,p < 0.003,p < 0.0001, and p < 0.0001, respectively). Residents' satisfaction from living nursing homes and participation in physical exercise were significant predictors of WHOQOL-BREF scores for those that participated in this study. (C) 2007 Elsevier Ireland Ltd. All rights reserved.
Keywords: disability in the elderly; quality of life (QoL); World Health Organization's Quality of Life-BREF (WHOQOL-BREF); nursing home; BODY-MASS INDEX; OLDER-PEOPLE; WHOQOL-BREF; CARE; HEALTH